Inovasi Pembelajaran Pendidikan Islam Berbasis Etnopedagogi dalam Menanamkan Nilai-Nilai Moral Anak di Era Disrupsi - Hasan Al Banna; Riki Faisal; Neneng Nurhasanah; Gina Kania; Marwah Triyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The era of disruption demands innovation in Islamic education to address the moral challenges faced by elementary school children. Amidst globalization and technological advancements, it is crucial for learning to remain grounded in local cultural values aligned with Islamic teachings. This study aims to describe the forms, strategies, and effectiveness of ethnopedagogy-based Islamic education learning innovations in instilling moral values in elementary school children. This study employed a qualitative approach with a case study method at SDIT Buah Hati Islamic School. Data were collected through observation, in-depth interviews, and documentation, which were then analyzed using the Miles and Huberman interactive model. The results show that learning innovations are implemented through the integration of local cultural values into Islamic education materials, the application of participatory learning methods, and teacher role models based on traditional noble values. This innovation has proven effective in shaping students' moral character, including honesty, responsibility, caring, and respect. These findings imply the importance of developing ethnopedagogy-based curricula and learning strategies in Islamic education. This innovation is able to bridge local values and Islamic principles in shaping children's morality contextually. This study recommends strengthening teachers' capacity in implementing an ethnopedagogical approach systematically.